Cystic Fibrosis in An Infant: Presented as Pseudo Bartter Syndrome (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2016)
Cystic Fibrosis (CF) can involve multiple organs although the most commonly affected systems are respiratory and gastrointestinal ones. In infancy it can also present as Pseudo Bartter Syndrome which is characterized by hyponatremic, hypochloremic, hypokalamic metabolic alkalosis without renal tubular pathology. We report a 5 month old boy who had history of recurrent episodes of dehydration due to vomiting and recurrent respiratory infection. His biochemical parameters suggestive of Pseudo Bartters Syndrome. Initial sweat chloride test was normal 16 mEq/L whereas the repeated test revealed Sweat chloride concentration of 107 mEq/L. The cystic fibrosis mutation analysis revealed F508 del homozygosity for the Cystic Fibrosis Transmembrane Regulator (CFTR) gene. Cystic fibrosis should be always considered in any infant with metabolic alkalosis and hyponatremic hypochloremic dehydration, whether or not there are association with pulmonary and /or gastrointestinal symptoms. Early diagnosis is essential in improving the prognosis and long term survival of these children.Chatt  Shi Hosp Med Coll J; Vol.15 (1); Jan 2016; Page 57-59